Dependency of spanish urban hotels on Booking.com - Mellinas, Juan Pedro (Tourism Analysis, 2019)
There is an increasing dependency of hotels on online travel agencies (OTAs) around the world, particularly in Booking.com when we focus on Europe, but there is a lack of information about accurate data related to market share of OTAs. Moreover, it is not possible to access individual information about hotels' dependency on OTAs because it is confidential. An indicator, based on the number of reviews of each hotel on Booking.com (RpR), is proposed as a proxy for hotel reservations. It does not provide the exact number of reservations made through Booking.com , but allows comparing dependency levels. Results from Spanish urban hotels suggest higher dependency percentage than in previous research using surveys at a European level. Independent hotels and hotels with small size or low star category arc clearly more dependent on Booking.com . The RpR could be used as a benchmarking tool for hotels when comparing with competitors and can also function as an indicator of the evolution of the dependence on OTAs for individual hotels. The methodology described can be applied to other OTAs that have a similar reviewing system, like Expedia, Agoda or FIRS, which would provide estimations about competitors' distribution mix.
Keywords: reviews; hotels; dependency; booking.com; online travel agencies (OTAs); Emerging; Scopus